ASEAN INVESTMENT DISPUTE SETTLEMENT MECHANISM THROUGH REGIONAL INVESTMENT COURT FRAMEWORK - Vida Azaria; Prita Amalia (Fakultas Hukum Universitas Padjadjaran, 2023)
In this paper, the authors provide an overview and comparison of the ASEAN dispute settlement mechanism (DSM) in the 2004 Protocol on EDSM and the ASEAN Comprehensive Investment Agreement (ACIA 2009) and review ASEAN's experience with investor-state dispute settlement (ISDS). The paper then examines the challenges and possibilities of restructuring ASEAN DSM through a Regional Investment Court. This includes discussing the potential benefits and drawbacks of such restructuring and its potential implications for regional integration. Finally, the paper offers some thoughts on possible future developments in this area, including the potential impact of a Regional Investment Court on the overall stability and effectiveness of the ASEAN DSM.